2011
DOI: 10.1007/s00256-011-1110-x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic radiographic quantification of hand osteoarthritis; accuracy and sensitivity to change in joint space width in a phantom and cadaver study

Abstract: ObjectiveTo validate a newly developed quantification method that automatically detects and quantifies the joint space width (JSW) in hand radiographs. Repeatability, accuracy and sensitivity to changes in JSW were determined. The influence of joint location and joint shape on the measurements was tested.MethodsA mechanical micrometer set-up was developed to define and adjust the true JSW in an acrylic phantom joint and in human cadaver-derived phalangeal joints. Radiographic measurements of the JSW were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Most clinical trials of rheumatoid arthritis (RA) have overcome this error by utilizing positioning frames with permanently embedded left-right markers designed in such a way as to make it impossible to image a hand with the wrong marker. As with knee radiography, changes in the position of the hand can change JSW values 8,9 and are likely to affect measurements of osteophytes. The use of a hand positioner is therefore recommended so that consistency is maintained both cross-sectionally and longitudinally.…”
Section: Radiographymentioning
confidence: 99%
See 3 more Smart Citations
“…Most clinical trials of rheumatoid arthritis (RA) have overcome this error by utilizing positioning frames with permanently embedded left-right markers designed in such a way as to make it impossible to image a hand with the wrong marker. As with knee radiography, changes in the position of the hand can change JSW values 8,9 and are likely to affect measurements of osteophytes. The use of a hand positioner is therefore recommended so that consistency is maintained both cross-sectionally and longitudinally.…”
Section: Radiographymentioning
confidence: 99%
“…There are no published reports that quantify the effect of radiographic technique (mA and kVp) on measurement error; however these factors are unlikely to alter measurements of JSW or osteophytes unless the quality is significantly compromised. Huetink et al 9 reported no systematic change in JSW as a function of the film-to-focus distance (FFD) for FFD covering 110e120 cm. Indeed as long as the hand is placed directly on top of the detector and the FFD is consistent at all time points for all patients, the magnification factor will change negligibly as a function of FFD.…”
Section: Radiographymentioning
confidence: 99%
See 2 more Smart Citations
“…During follow-up visit after 10 years standardized weight bearing posterior-anterior knee radiographs in a semiflexed position and lateral radiographs of the knee were made. Knee radiographs of the initially affected knee were scored for the presence and severity of OA using the 0-4 Kellgren and Lawrence (KL) scoring system [29]. Radiographic knee OA was considered to be present in patients with a KL score of 2 or higher.…”
Section: Knee Radiographsmentioning
confidence: 99%